Homeostatic glucocorticoid signaling in airway smooth muscle: A roadmap to asthma pathogenesis - Grunstein, Michael M. (Frontiers in Endocrinology, 2023)
Homeostasis is the self-regulating process by which the body maintains internal stability within a narrow physiological range (i.e., “normality”) as it dynamically adjusts to disruptive influences. Thus, whereas homeostasis maintains bodily health, disrupted homeostasis at the tissue or systemic level leads to disease. Airway smooth muscle (ASM) is the pivotal site of disrupted homeostasis in asthma. While extensive research has greatly expanded our understanding of ASM behavior under pro-asthmatic conditions, the cellular signaling mechanisms that underlie ASM homeostasis under these conditions remain elusive. Based on a broad collection of published studies, a homeostasis mechanism intrinsic to ASM and exhibited under inflammatory and non-inflammatory pro-asthmatic conditions is identified herein. Central to this mechanism is the novel unifying concept that the pro-asthmatic-exposed ASM can independently generate its own active glucocorticoid (i.e., cortisol), produce its own newly activated glucocorticoid receptors for the steroid, and, accordingly, use this molecular strategy to homeostatically prevent induction of the asthmatic state. This article addresses the experimental evidence that underlies the proposed homeostatic glucocorticoid signaling mechanism in ASM, followed by a discussion and depiction of the feed-forward and feedback intrinsic ASM signaling circuitry that constitutes the homeostatic state. The proposed mechanism offers a practical roadmap for future basic and translational research aimed at identifying potential key site(s) of disrupted ASM homeostasis leading to asthma.